PEMBINAAN ORANG TUA TERHADAP ANAK TUNGGAL DI SMPN 3 PANCUNG SOAL KABUPATEN PESISIR SELATAN - Lestari, Silva; Arief, Asmaiwaty; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Problems studied is coaching parents of an only child who does not give the opportunity to attend social events, do not give freedom of action. It is not appropriate to the circumstances which ought to give the child the opportunity for social activities, and providing freedom of action. The research was conducted in SMPN 3 Pancung Soal Kabupaten Pesisir Selatan. The research objective is to describe: 1) Development of parents of only child in social skills. 2) Development of parents of children in the freedom of action. This research is a qualitative case study. Key informants in this study were 2 people which only child SMPN 3 Pancung Soal Kabupaten Pesisir Selatan. Additional informants were parents. The instruments used were interviews, observation, document study. Data analysis is data reduction, data display, conclusion. The result: 1) Development of Â parents of the only children in social skills has not been right, 2) Development of parents of the only children in the freedom of action is not yet right. Based on the results of the study suggested: the only begotten son, may respond with positive coaching parents. Parents, in order to provide appropriate guidance to the child.